Sistema de recomendação para promoção de redes homófilas baseadas em valores culturais: observando o impacto das relações homofílicas na reciprocidade apoiada pela tecnologia - Oliveira, Jônatas Leite de (Universidade Federal de São Carlos, 2013)
Nowadays, with ICTs permeating social relations and work, it is necessary to understand how relationships influence the socially established professional dynamics in the workspace. One should also consider that the impact of social relationships on work supported by ICT. From the understanding of co-existing dependencies in social relationships of different natures as friendship and cooperation, and its expression in media technology, it can search the support of ICT in decision making and search for information to foundation of these decision making based the values of friendship and trust between individuals. This work is developed to this understanding of co-dependency, enabling develop future recommender systems based on trust. Based on the results of research on behavior at work and interpersonal relationships conducted in a community of health professionals in a hospital partner in this research, we analyze here the actions of reciprocity among professionals considering their social relationship. The research challenge is to understand the existing social structures in the community and identify whether these structures promote the practices of reciprocity in the workplace. This research discusses the relationship between the established social homophily (the tendency that two people who have similar values and experiences have to establish friendship) and reciprocity expressed in systems based on ICTs in the workplace. Applied to hospital staff, is observed as homophily between health professionals influence the reciprocity stimulation when has adopt ICTs in the workplace. The collected data are insufficient for conclusions on the co-dependencies, but indications point to be the target of future research. It was found that mostly of reciprocal pairs are homophilous, and that among these pairs there is a trend of pairs with greater degree of homophily present more intense reciprocity than pairs with lesser degrees of homophily.
Keywords: Homofilia; Reciprocidade; TIC; Amizade; Similaridade entre indivíduos; Ambiente de trabalho; Homophily; Reciprocity; ICT; Friendship; Similarity between individuals; Workplace; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::TEORIA DA COMPUTACAO::ANALISE DE ALGORITMOS E COMPLEXIDADE DE COMPUTACAO